2017
DOI: 10.1039/c6ra28585f
|View full text |Cite
|
Sign up to set email alerts
|

Tube in tube ZnO/ZnCo2O4 nanostructure synthesized by facile single capillary electrospinning with enhanced ethanol gas-sensing properties

Abstract: Tube in tube nanostructure of ZnO/ZnCo2O4 was achieved using electrospinning technology. The complex tubular structure and n–p heterojunction are potential reasons for the excellent gas sensing performance of ZnO/ZnCo2O4 tube in tube nanostructure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(10 citation statements)
references
References 29 publications
(69 reference statements)
1
9
0
Order By: Relevance
“…It is reported that In-doped 3DOM ZnO showed a response of 88 to 100 ppm ethanol at the optimal working temperature of 250 °C, and Co-doped ZnO nanorods showed a response as high as 129 to 100 ppm ethanol at 350 °C . SnO 2 –ZnO hetero-nanofibers and Fe-doped lotus-like ZnO showed responses of 78 and 24 to 100 ppm ethanol at 300 and 400 °C, , respectively. A few ZnO-based sensors with working temperature lower than 200 °C were also reported.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that In-doped 3DOM ZnO showed a response of 88 to 100 ppm ethanol at the optimal working temperature of 250 °C, and Co-doped ZnO nanorods showed a response as high as 129 to 100 ppm ethanol at 350 °C . SnO 2 –ZnO hetero-nanofibers and Fe-doped lotus-like ZnO showed responses of 78 and 24 to 100 ppm ethanol at 300 and 400 °C, , respectively. A few ZnO-based sensors with working temperature lower than 200 °C were also reported.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table , 5%Co/ZnO-300 has a higher electron carrier concentration, larger Hall mobility, and lower resistivity than ZnO-300. The higher electron concentration is beneficial to the adsorption of more O 2 , which can contribute to the enhancement of the gas-sensing performance. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An illustration of the electrical circuit of the sensor is exhibited in Figure S4 (in the Supporting Information). During exposure to gas, a change in the resistance of the sensors’ circuit will result from the chemisorption reaction of the sensing material with gas molecules, which will be measured and presented as the output voltage ( V out ) …”
Section: Methodsmentioning
confidence: 99%
“…The spinning starts after the application of a high voltage between the syringe needle and the collector. The feed rate of the polymeric solution, the applied voltage, the distance work, and the physicochemical properties of the polymeric solution are some of the critical parameters of the electrospinning process that must be adjusted . Under the effect of the applied electrical field, a conical fluid shape ( a Taylor cone) will form at the tip of the syringe needle, and at a critical value of the applied voltage, the charged polymeric solution will overcome the surface tension forces causing a jet to erupt from the tip of Taylor cone.…”
Section: Electrospinning Technique and Its Parametersmentioning
confidence: 99%